Orchid itineraries of Augustus R. Endrés in Central America: a biographic and geographic sketch - Ossenbach, Carlos; Pupulin, Franco; Jenny, Rudolf (Lankesteriana: International Journal on Orchidology, 2010)
A.R. Endrés, as he was known until recent research revealed most of his relevant biographical data, was the most important orchid collector to visit Costa Rica. Besides collecting the type specimens for some one hundred new orchid species, he discovered, described and illustrated thousands of orchid plants, most of which remained still undescribed during his life time. One of the outstanding aspects of the collections made by Endrés in just a few years in the post-colonial Costa Rica of the Nineteenth century is his impressive knowledge of the country, in terms of geographical coverage, which in several cases extended beyond the limits of the already explored territories. The present paper presents for the first time the most important biographical facts about Endrés’ life and his orchidologic work in Central America. The main exploratory routes made by Endrés are highlighted in the framework of the social geography of his time, and a complete catalogue of the localities where he made his orchid collections, referenced to modern geographical coordinates, is presented.